2022
DOI: 10.1002/ejoc.202201105
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Symmetrically and Unsymmetrically Substituted Cationic Diborane(4) Compounds with Distinct Structural Motifs and Properties

Abstract: The introduction of electron‐donating, bridging guanidinate substituents in diborane(4) compounds allows the synthesis of a variety of new cationic diborane(4) compounds. In this work, strategies for the directed synthesis of cationic di‐ and tetraboron compounds are presented, leading to the synthesis and complete characterization of several new compounds with distinct structural motifs, all exhibiting BII atoms directly bound to each other. Hence, we report on tetracationic donor‐acceptor cyclophanes with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…With 1.7097(1) Å, the BÀ B bond length is in a typical range for related BÀ B single bonds. [24] In this case, no electron-transfer is involved. The conversion was followed by 1 H NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…With 1.7097(1) Å, the BÀ B bond length is in a typical range for related BÀ B single bonds. [24] In this case, no electron-transfer is involved. The conversion was followed by 1 H NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The cyclic rings of 5 and 6 exhibit a larger cavity than the previously reported polycationic cyclophanes with two or three diborane units that result from reaction of the ditriflato-diborane B 2 (hpp) 2 (OTf) 2 with di-or tri-pyridines. [24][25][26]…”
Section: Resultsmentioning
confidence: 99%
“…DFT computations suggested that the boron‐boron dehydrocouping with iodine is thermodynamically favored. Additionally, they successfully synthesized a series of guanidinate group‐stabilized cationic diboron species and other derivatives [61–64] …”
Section: Neutral B−b Bonded Diboron Compoundsmentioning
confidence: 99%
“…Additionally, they successfully synthesized a series of guanidinate group-stabilized cationic diboron species and other derivatives. [61][62][63][64] Including BÀ B bond in the small ring system is an excellent way to increase its reactivity. Xie and co-workers reported a carborane-fused four-membered boracycle 67 through the reaction of 1,2-Li 2 -o-carborane with B 2 Br 4 (SMe 2 ) 2 (Scheme 19).…”
Section: R E V I E W T H E C H E M I C a L R E C O R Dmentioning
confidence: 99%